Geniposide Possesses the Protective Effect on Myocardial Injury by Inhibiting Oxidative Stress and Ferroptosis via Activation of the Grsf1/GPx4 Axis - Shen, Yuehong; Wang, Xindong; Shen, Xinyu; Wang, Yue; Wang, Shulin; Zhang, Yunyun; Yao, Xiaoming; Xu, Yijiao; Sang, Ming; Pan, Jiamin; Qin, Yu; Zhou, Qian; et al. (Frontiers in Pharmacology, 2022)
Reactive oxygen species (ROS) produced in the ischemic myocardium can induce cardiomyocyte injury and death, resulting in cardiac remodeling. Ferroptosis, known as a newly type of cell death caused by iron-dependent oxidative stress, which is an essential death mechanism in cardiomyocytes. However, it is unclear whether oxidative stress products can further induce ferroptosis and aggravate cardiomyocyte injury. Geniposide (GEN), a major active component of Gardenia jasminoides J. Ellis, possesses the natural antioxidant activity and cardioprotective effect. Herein, we evaluated the role of ferroptosis in myocardial oxidative injury and the protective effect of GEN on myocardial ferroptosis. We first detected iron overload, massive ROS, and lipid peroxidation in ferric ammonium citrate (FAC)-treated cardiomyocytes, which were typical characteristics of ferroptosis. The iron overload-induced oxidative stress and ferroptosis aggravated cardiomyocyte injury, which were significantly alleviated by GEN treatment. Similar phenotypic changes of ferroptosis were consistently discovered in hydrogen peroxide (H2O2)-induced cells, which were reversed by GEN treatment as well. Interestingly, the RNA-binding protein Grsf1, which directly upregulated Gpx4 at the translational level, was activated by GEN following myocardial oxidative injury. The specific knockdown of Grsf1 increased their sensitivity to ferroptosis and weakened the cardioprotective effect of GEN in H2O2-treated cardiomyocytes. Moreover, GEN treatment reduced iron overload and lipid peroxidation in myocardial infarction (MI) rats, thereby fighting against the cardiac ischemic injury. Collectively, our study revealed the pathogenesis of oxidative stress and ferroptosis associated with myocardial ischemia, and indicated the antioxidant and anti-ferroptosis effects of GEN on preventing myocardial injury by activating the Grsf1/GPx4 axis, serving as a potential therapeutic target.